Hot or Not: Response Inhibition Reduces the Hedonic Value and Motivational Incentive of Sexual Stimuli - Ferrey, Anne E.; Frischen, Alexandra; Fenske, Mark J. (Frontiers in Psychology, 2012)
The motivational incentive of reward-related stimuli can become so salient that it drives behavior at the cost of other needs. Here we show that response inhibition applied during a Go/No-go task not only impacts hedonic evaluations but also reduces the behavioral incentive of motivationally relevant stimuli. We first examined the impact of response inhibition on the hedonic value of sex stimuli associated with strong behavioral-approach responses (Experiment 1). Sexually appealing and non-appealing images were both rated as less attractive when previously encountered as No-go (inhibited) than as Go (non-inhibited) items. We then discovered that inhibition reduces the motivational incentive of sexual appealing stimuli (Experiment 2). Prior Go/No-go status affected the number of key-presses by heterosexual males to view erotic-female (sexually appealing) but not erotic-male or scrambled-control (non-appealing) images. These findings may provide a foundation for developing inhibition-based interventions to reduce the hedonic value and motivational incentive of stimuli associated with disorders of self-control.